'All Those Stories, All Those Stories': How Do Bosnian Former Child Refugees Maintain Connections to Bosnia and Community Groups in Australia?. Issue 2 (4th May 2018) - Green, Sarah
Abstract: This article draws on oral histories from my PhD research to explore how six teenagers, now adults, remember their arrivals in Australia as child refugees from Bosnia. It examines their relationships with other people from Bosnia and the former Yugoslavia, including community groups, and how these relationships have changed over time. In examining these narratives, issues of intergenerational differences are highlighted, with interviewees positioning their experiences in relation to both their parents and their second-generation peers. Finally, it explores how former refugees maintain their relationships with family and friends in Bosnia, suggesting that these transnational connections provide them with as much familiarity and comfort as they do feelings of alienation.